Thalassemia and Hemoglobinopathies in a group of ethnic minority in Vietnam - Nguyen, Hoa Van; Sanchaisuriya, Kanokwan; Siridamrongvattana, Sirivara; Vo, Thang Van; Nguyen, Duyen Mau; Phan, Hoa Thi Thuy; Sanchaisuriya, Pattara; Fucharoen, Supan; Fucharoen, Goonnapa; P. Schelp, Frank; và c.s. (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
.